Development of a Smash Roll Training Model for Sepak Takraw Students of Sports Science - Sardiman Sardiman; Ryo Sinung Primadana; Rivalwan Rivalwan; Krisyanto Batong Lumbaa; Addriana Bulu Baan (Newinera Publisher, 2026)
This research was designed to elaborate a smash roll training model on Sports Science students of Muhammadiyah University Palu, class 2022, that could be utilized as a hands-on guide in the learning of sepak takraw. The research and development model that was used in the study was an adaptation of the Borg and Gall model. Needs analysis, product design, expert validation, product revision, small group testing, large group testing and final refinement were all part of the development process. The necessity of the model was caused by the problems of students to coordinate their movement, create explosive jumping force and do body rotation with the confidence when smash roll is being performed. The needs analysis also revealed that the majority of the students believed that it was necessary to develop a smash roll training model. The first product was tested by professionals and was later revised and tested on students. The small group trial also gave an overall score of 57.5 percent which meant that the first product was still in need of some improvement. Upon revision, the large group trial indicated a significant improvement, to 86.22 percent, and this represents that the formulated model had reached a high level of practicality to be used in the learning process. Based on these findings it is evident that the smash roll training model is practical and can be applied as a benchmark in the training of sepak takraw among university students.